Pengaruh Pemberian Tepung Indigofera Sebagai Pengganti Bungkil Kedelai Dan Dedak Dalam Ransum Terhadap Kualitas Karkas Entog (Cairina Moschata) - Abdul Jalil; Dini Widianingrum; Rachmat Somanjaya (Tropical Livestock Science Journal, 2023)
This research was carried out on March 30, 2021 to April 27, 2021, located in Darma District, Kuningan Regency, West Java Province, which is located at the coordinates 7°02'09.4” South Latitude 108°24'24'20.6” East Longitude. The purpose of this study was to analyze the effect of the level of indigofera flour ration on the carcass quality of muscovy duck. The study was conducted experimentally using Completely Randomized Design (CRD). 80 ducks are drawn by lot to be placed in a cage which has been divided into 20 sections, each section filled with 4 ducks. This study consisted of five types of treatment, namely PO without the addition of indigofera leaf meal (TDI) as control feed, P1 25% added TDI, P2 50% added TDI, P3 75% added TDI, and P4 100% added TDI. The variables observed in the study were the carcass quality of muscovy duck, including measurements of body composition, carcass composition, and non-carcass composition measurements. The research data were analyzed using the Variety Print or Anova (Analysis of Variance) and further tested using the Duncan Multiple Range Test. The results showed that feeding indigofera flour in the ration had a significant effect (P<0.05) on feather weight, dressing weight, carcass weight, chest weight, and non-carcass weight. However, overall the addition of TDI in the ration reduced the carcass quality of the muscovy duck. Therefore, it can be concluded that the addition of TDI as a substitute for soybean meal and bran in the eggplant ration is less effective and can reduce the quality of the eggplant carcass.